STRUKTUR MODAL TRADISIONAL DAN IMPLIKASINYA TERHADAP TEORI SIGNALING - Listiarini, Listiarini; Audrey Lawrence Ginting; Hafiza Zahra Camilla (PT. Saha Kreasi Indonesia, 2025)
Capital structure is a strategic financial decision that determines the proportion of debt and equity used to finance a firm’s operations. This decision directly influences the cost of capital, financial risk, and overall firm value. This study aims to analyze the traditional approach to capital structure assessment and to examine its implications for signaling theory within the context of modern capital markets. The research employs a library research method by reviewing relevant scholarly journals, textbooks, and academic publications. The findings indicate that the traditional approach emphasizes the existence of an optimal capital structure capable of minimizing the weighted average cost of capital (WACC), whereas signaling theory views financing decisions as indicators of managerial quality. The integration of both theories highlights that leverage choices can serve as strong signals to investors, thereby affecting market perceptions and ultimately influencing firm value.